14+6t=-2/3t

Simple and best practice solution for 14+6t=-2/3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+6t=-2/3t equation:



14+6t=-2/3t
We move all terms to the left:
14+6t-(-2/3t)=0
Domain of the equation: 3t)!=0
t!=0/1
t!=0
t∈R
We get rid of parentheses
6t+2/3t+14=0
We multiply all the terms by the denominator
6t*3t+14*3t+2=0
Wy multiply elements
18t^2+42t+2=0
a = 18; b = 42; c = +2;
Δ = b2-4ac
Δ = 422-4·18·2
Δ = 1620
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1620}=\sqrt{324*5}=\sqrt{324}*\sqrt{5}=18\sqrt{5}$
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(42)-18\sqrt{5}}{2*18}=\frac{-42-18\sqrt{5}}{36} $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(42)+18\sqrt{5}}{2*18}=\frac{-42+18\sqrt{5}}{36} $

See similar equations:

| b/2-7=-5 | | 7x+13=5x+5 | | 3(2w-9)=19 | | 5k-3=67 | | 8x=8=25 | | 2(5x)=8(3x) | | 2=(5p+7)–(p+2) | | -2(1-4n)=3n+8 | | 16+4x=-8-5(1+5x) | | C(x)=0.6+30 | | t-12-3t=60 | | −6x+18=−6. | | -6x-4=-8 | | |4x−2|+1=15 | | 7.5c-27c=-6 | | -8a+8a=0 | | 9-(1s-)=2s+6 | | 19-(2x+3)=2(x+3)+x | | 19.35-5.5w=16w | | -2r+12=20 | | 3x-12=3x+17 | | 18=-4m-6 | | -20+11w=19+13w-5 | | 4n+4=2(-n+2) | | −9x+6=2x−2 | | 4t+20=6 | | -12-3k=-1k+20 | | 9.42d=37.69 | | 8(3t-2)=4(7t-1) | | 20=5+2.25x | | x²=900 | | `4(2-b)=-12` |

Equations solver categories